Microstructural and mechano-tribological behavior of Al reinforced SiC-TiC hybrid metal matrix composite. (2020) - Kumar, Alip; Yeasin Arafath, Md.; Gupta, Pallav; Kumar, Devendra; Mustansar Hussain, Chaudhery; Jamwal, Anbesh
Abstract: At present time aluminum matrix composites are widely used in automobile sectors, aerospace, and other engineering applications. The aim of this present study is to develop aluminum reinforced SiC-TiC hybrid metal matrix composites by liquid stir casting process. It also investigates the effect of hybrid ceramic reinforcements on the microstructural, mechanical and tribological behavior of composites. In present study, for composites SiC content is fixed as 1 wt% and TiC content is varied as (1, 1.5, 2 and 2.5 wt%). It is found that increase in the reinforcement content of SiC-TiC particles increases the hardness and decreases the density of composites. Improvement in wear resistance is also seen at higher reinforcement content. It is expected that this composite is beneficial in the development of lightweight composites for aerospace applications.